Development of a Physics Integrated STEM Meguru Model Oriented by Local Wisdom for Students' Creative Thinking Skills - Eka Dewi; Finta Amalinda; Daud K. Walanda; Mohammad Jamhari; Marungkil Pasaribu (Postgraduate, University of Mataram, 2025)
One of the existing learning approaches is challenge-based learning (CBL) which modified to Meguru, that encourages students to think critically and creatively in solving real problems. The STEM integrated CBL physics learning model based on local wisdom is present as an alternative to overcome these challenges. The main aim of this research is to develop a STEM-integrated physics challenge based learning model oriented to local wisdom towards quality students' creative thinking skills with valid, practical and effective criteria. This research is the Borg and Gall development model that was carried out through expert validation via FGD to obtain suggestions and input in order to revise the model, so that the valid Meguru model was obtained. The experts provide recommendations that the Meguru learning model was suitable for use with improvements (LDP). Validation of learning tools, obtained model implementation sheet with a score of 1.00 (very valid), teaching module with a score of 3.78 (very valid), student activity sheet (LKPD) with a score of 3.94 (very valid), student activity observation sheet with a score of 1 .00 (very valid), and the student response questionnaire was 98.66 (very valid). In the testing phase of the model's effectiveness, students' creative thinking skills were obtained with an average score of 97.50. The score obtained in the very good category shows that the learner's goals were achieved. where the Meguru learning model is effectively used in Physics learning. The type of research is development research or Research and Development (R&D)